Analysis of Anthocyanins Extracted from the Acai Fruit (Euterpe oleracea): A Potential Novel Vital Dye for Chromovitrectomy - Cristiane S. Peris; Rafael R. Caiado; Acácio Alves Souza Lima-Filho; Eduardo B. Rodrigues; Michel Eid Farah; Mariana Batista Gonçalves; Bruno de Queiroz Alves; Joao Guilherme Palma Urushima; Raul Ragazzi; Mauricio Maia (Journal of Ophthalmology)
Purpose. To classify and quantify anthocyanins in a vital dye extracted from the acai fruit (Euterpe oleracea), adjust pH and osmolarity, and perform lyophilization to develop a new chromovitrectomy dye. Methods. Three dye concentrations 10%, 25%, and 35% (equivalent to 100, 250, and 350 mg of lyophilized acai fruit pulp extract samples) were evaluated when diluted in 1 ml of phosphate-buffered solution (pH 7 and 300 mOsm). The dye was analyzed by mass spectrometry and high-performance liquid chromatography (HPLC) to identify and quantify anthocyanins molecules. Results. The pH and osmolarity correction and lyophilization were performed without damaging the anthocyanin molecular structure. Mass spectrometry confirmed the presence of five anthocyanins in the three concentrations of the dye. Cyanidin-3-O-glucoside was the major anthocyanin found. HPLC showed that the concentration of anthocyanin was similar, independent of the dye concentration tested. Conclusions. Lyophilization and the correction of pH and osmolarity (7.00 and 300 mOsm, resp.) were performed successfully. Five anthocyanins are present in the dye from the acai fruit. The major anthocyanin is cyanidin-3-O-glucoside. Independent of the dye concentration tested, the anthocyanin concentration was similar. Standardized chemical characteristics of this new dye may allow its use during chromovitrectomy in humans.